Is Pooled Data Analysis of Ventral and Incisional Hernia Repair Acceptable? - Köckerling, Ferdinand; Schug-Paß, Christine; Adolf, Daniela; Reinpold, Wolfgang; Stechemesser, Bernd (Frontiers in Surgery, 2015)
Abstract Purpose: In meta-analyses and systematic reviews comparing laparoscopic with open repair of ventral hernias, data on umbilical, epigastric and incisional hernias are pooled. Based on data from the Herniamed Registry, we aimed to investigate whether the differences in the therapy and treatment results justified such an approach. Methods: Between 1 September 2009 and 31 August 2013, 31,664 patients with a ventral hernia were enrolled in the Herniamed Hernia Registry. The implicated hernias included 16,206 umbilical hernias, 3,757 epigastric hernias, and 11,701 incisional hernias. Data on the surgical techniques, postoperative complication rates and one-year follow-up results were subjected to statistical analysis. Results: The laparoscopic IPOM technique was used significantly more often for incisional hernia than for epigastric hernia, 31.3 % vs. 24.0 %, respectively, and was used for 12.9 % of umbilical hernias (p < 0.0001). Likewise, the open technique with suturing of defect was used significantly more often for umbilical hernia than for epigastric hernia, 56.1 % vs. 35.4 %, respectively, and was used for 12.5 % of incisional hernias (p < 0.0001). The postoperative complication rates of 3.2 % for umbilical hernia and 3.5 % for epigastric hernia were significantly lower than for incisional hernia, at 9.2 % (p < 0.0001). That was also true for the reoperation rates due to postoperative complications, of 1.0 % vs. 1.2 % vs. 4.2 % (p < 0.0001). The one-year follow-up revealed significantly higher recurrence rates as well as rates of chronic pain needing treatment of 6.3 % and 7.9 %, respectively, for incisional hernia, compared with 4.1 % and 4.3 %, respectively, for epigastric hernia, and 2 % and 1.9 %, respectively, for umbilical hernia (p < 0.0001). Conclusion: Since significant differences were identified in the therapy and outcome between umbilical, epigastric and incisional hernias, scientific studies should be conducted only for a single hernia type.